ANALYSIS OF THE APPLICATION OF OCCUPATIONAL HEALTH AND SAFETY (OHS) CONSTRUCTION IN THE CONSTRUCTION PROJECT OF THE BRI PADANG CITY REGIONAL OFFICE BUILDING - Satria Refindo; Annisa Prita Melinda (Jurnal Applied Science in Civil Engineering, 2022)
The research that will be discussed is an analysis of the application of K3 construction and its obstacles to the BRI Bank regional office project. The results of observations in the field found several problems that could cause losses for both parties, this is related to the application of K3 to the project. The type of research to be carried out is a type of quantitative descriptive research. Researchers use the subjects of people as data for the research to be carried out, namely filling out questionnaires by staff or workers in the scope of the project, to determine the sample used purposive sampling technique with the use of the Slovin formula, the number of samples of 55 respondents was found. Before the research is carried out, it is necessary to test a questionnaire in the form of validity and reliability tests. In this study, we will use SPSS.26 and Excel 2010 programs to help process statistical data in research. After obtaining statistical data followed by data analysis, data analysis was carried out by indicators of research instruments that received scores, namely human resources 95.45%, equipment and work clothes 94.18%, Work Environment Health 89.09%, and work environment facilities 84.09%. Each indicator included in the score assessment is very effective. Barriers to K3 implementation by workers 10.55% and Barriers to K3 implementation by companies 20.73%. Each indicator is included in the score assessment Ineffective. In the application of K3, the highest percentage value is HR, while in the Obstacle to the highest percentage value, namely the Obstacle to the Implementation of K3 by the Company.